The Beneficial Effects of Computer-Based Cognitive Training in Parkinson's Disease: A Systematic Review. (14th January 2020) - Nousia, Anastasia; Martzoukou, Maria; Tsouris, Zisis; Siokas, Vasileios; Aloizou, Athina-Maria; Liampas, Ioannis; Nasios, Grigorios; Dardiotis, Efthimios
Abstract: Background: Cognitive dysfunction is one of the most prevalent non-motor aspects of Parkinson's disease (PD). The present review focuses on published studies investigating the effect of computer-based cognitive training (CT) on neuropsychological performance in PD. Methods: A systematic search of the PubMed database and Google Scholar was carried out. Randomized controlled studies published before September 2019, investigating the effect of computer-based CT (regardless of the comparator, active or placebo) on PD patients were included. Literature search, data extraction, and Risk of Bias (RoB) evaluation (based on the RoB Cochrane tool for Randomized Trials) were performed by two authors (A.N. and M.M), independently. Results: Among 30 full-texts assessed for eligibility, seven articles fulfilled the inclusion criteria and were involved in the qualitative analysis. The main outcomes of the retrieved studies (all studies used similar cognitive rehabilitation methodologies) were indicative of cognitive improvement in most cognitive domains, particularly memory, executive function, processing speed, and attention, that is, the domains primarily impaired in the disease. Conclusion: Multidomain CT, which is exclusively based on computer software, leads to measurable improvements in most cognitive domains affected in patients with PD. The present review is the first to include studies assessing the effect of computer-based CT techniques without deploying CT with paper-pencil techniques. Limitations originate mainly due to the heterogeneity among included studies (differences in CT softwares, PD stages, number, and duration of training sessions.